Growing a Culturally Responsive Tertiary Programme in Psychology. Issue 1 (August 2019) - Britt, Eileen; Macfarlane, Angus; Macfarlane, Sonja; Naswall, Katharina; Henderson, Jacki
Abstract : This paper provides a description of a postgraduate clinical psychology training programme's journey towards becoming more biculturally responsive and how the learnings from this have been applied to the wider Department of Psychology at the University of Canterbury (UC), Aotearoa New Zealand (NZ). The paper includes a discussion of cultural competency, and frameworks which have been proposed as a way to blend Western and Māori knowledge and clinical and cultural practices. The reasons for introducing the changes, the process of change and the actual changes are described, together with a discussion of the outcomes of the changes. Key principles in undertaking the changes were that it was considered important that the process that was seen as an ongoing journey. Further guiding principles were that a graded, integrated approach was required, undertaken in partnership with Māori, and with a commitment to biculturalism before multiculturalism.